2019
DOI: 10.3389/fimmu.2019.01698
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Cytokine IL-33 Modulates the Cytotoxic CD8 T Lymphocyte Activity During Nutrient Deprivation by Regulation of Lineage-Specific Differentiation Programs

Abstract: IL-1 family member IL-33 exerts a variety of immune activating and regulating properties and has recently been proposed as a prognostic biomarker for cancer diseases, although its precise role in tumor immunity is unclear. Here we analyzed in vitro conditions influencing the function of IL-33 as an alarmin and a co-factor for the activity of cytotoxic CD8 + T cells in order to explain the widely discussed promiscuous behavior of IL-33 in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 62 publications
(60 reference statements)
1
19
0
Order By: Relevance
“…First, the bioactivity of IL-33 is limited in blood [33]. A study measured the serum levels of IL-33 in 30 healthy controls and found that all of the samples were undetectable (lowest limit of detection, 75 pg/mL) [33]. Future study addressing the role of IL-33 in AD can simultaneously measure IL-33 and its receptor ST2.…”
Section: Limitationsmentioning
confidence: 99%
“…First, the bioactivity of IL-33 is limited in blood [33]. A study measured the serum levels of IL-33 in 30 healthy controls and found that all of the samples were undetectable (lowest limit of detection, 75 pg/mL) [33]. Future study addressing the role of IL-33 in AD can simultaneously measure IL-33 and its receptor ST2.…”
Section: Limitationsmentioning
confidence: 99%
“…Alongside T cell receptor (TCR) signaling and IL-2 stimulation, IL-12 is described as the “third signal” for the expansion of cytotoxic T c 1 immune cell responses. One focus of our recent report was to understand the role of IL-33 and IL-12 in CD8 + T lymphocyte differentiation under nutrient deprivation ( 28 ). The function of IL-33 is dependent not only on TCR signaling, but also on the presence of IL-12.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has limitations. First, the bioactivity of IL-33 is limited in blood [28]. A study measured the serum levels of IL-33 in 30 healthy controls and found that all of the samples were undetectable (lowest limit of detection: 75 pg/ml).…”
Section: Discussionmentioning
confidence: 99%